Management of Student Administrative Services at Madrasah Tsanawiyah Nurul Hikam, Tanjung Jabung Barat, Jambi Province - Erlan Saputri; Siti Raudhatul Jannah; Fransisko Chaniago (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Student administrative service management is essential for maintaining orderly records, ensuring data accuracy, and sustaining educational activities in madrasahs. However, research examining these services as an integrated cycle of planning, organizing, implementation, and supervision in private Islamic junior secondary schools remains limited. This study aimed to describe the management of student administrative services, identify its supporting and inhibiting factors, and examine the solutions implemented at Madrasah Tsanawiyah Nurul Hikam, Tanjung Jabung Barat. A descriptive qualitative approach was employed, involving purposively selected informants comprising the madrasah head, administrative staff, teachers, and students. Data were collected through observations, interviews, and documentation and analyzed through data reduction, data display, and conclusion drawing and verification. Data credibility was established through source and technique triangulation. The findings indicate that student administrative services were delivered through the four management functions. Their implementation was supported by the leadership of the madrasah head, staff cooperation, and existing facilities, although limited personnel, facilities, service time, and the absence of written standard operating procedures constrained service effectiveness. The madrasah addressed these constraints by strengthening coordination, optimizing available facilities, gradually adopting information technology, conducting regular supervision, and improving administrative staff competence. The study concludes that effective student administrative services depend on the coordinated implementation of management functions, adequate institutional support, and sustained staff capacity development. These findings provide context-specific evidence for improving administrative governance in private madrasahs and highlight the importance of formalized procedures, human-resource development, and gradual digitalization in strengthening service quality.